Effects of emulsifier on feed process, feed quality, growth performance, relative organ weight and fat digestibility in broiler chicken - Cheah, Ying See (2016)
A feed production trial was conducted to study the effect of synthetic emulsifier and natural biosurfactant on feed process and quality of pelletized broiler feed. A corn-soy based broiler diet was formulated with fixed ratio 2:1 of oil-to-water with two types of emulsifiers, namely glyceryl polyethylene glycol ricinoleate synthetic emulsifier, and lysophosphatidylcholine natural biosurfactant. T1: Basal diet with no water and no emulsifier; T2: Basal diet with water and no emulsifier; T3: Basal diet with water and synthetic emulsifier glyceryl polyethylene glycol ricinoleate, which has been dispersed into an oil phase before added with water, pre-blended at 60 °C for 3 minutes to form a water-in-oil (w/o) emulsion; T4: Basal diet with water and a natural biosurfactant lysophosphatidylcholine as comparative treatment. The treatment diets were manufactured by a commercial feed mill. The electricity cost and meal temperature were measured during the process of milling. Composite samples were collected from different processed points, tested for physical properties, chemical stability and biostability of pelletized feed. Pellet quality of emulsifier supplemented diets was significantly (P<0.05) improved in crumble and pellet intact form. Correlation between emulsifier and pelletize processed cost was not observed in this present study. No deteriorate effect was observed in hydrolytic rancidity (AV), oxidation rancidity (PV),mold count, moisture content, water activity and water retention rate. However,percentage of starch gelatinization on pelletized feed was significantly (P<0.0001) improved in both types of emulsifier treated diets. These results demonstrated that the addition of emulsifier to broiler diet improved pellet quality to some extent although no significant difference between synthetic emulsifier and natural biosurfactant was observed. In the second experiment, a randomized complete block design study with 2x3 factorial arrangements was conducted to evaluate the response of exogenous emulsifier on broiler performance, relative organ weight and fat digestibility. A corn-soy based broiler diet was formulated with fixed ratio 2:1 of oil-to-water, supplemented with glyceryl polyethylene glycol ricinoleate (GPGR) synthetic emulsifier and lysophosphatidylcholine (LPC) natural biosurfactant. A total of 1,800 one-day-old Cobb 500 male broilers with nine treatments diet were adapted. T1: Basal diet with metabolizable energy (ME) 3,000 kcal/kg in starter (S) and 3,100 kcal/kg in grower (G);T2: Basal diet with ME 2,900 kcal/kg (S) and 3,000 kcal/kg (G); T3: Basal diet with ME 2,800 kcal/kg (S) and 2,900 kcal/kg (G); T4, T5 and T6 consisted of T1, T2 and T3 supplemented with GPGR; T7, T8 and T9 consisted of T1, T2 and T3 supplemented with LPC. The study was conducted 14 days for starter and 35 days for grower phase. The results of the experiment demonstrated that the effect of emulsifier on broiler performance was dependent on the ME level used in the diet formulations and ages of the bird. Emulsifier improved (P<0.05) FCR in starter phase at higher ME level, but was not significantly (P>0.05) improved at lower ME levels of diets. Correlation between emulsifier and low ME diet in FCR was not observed in this present study. AME and fat digestibility at all levels of ME were higher (P<0.05) in birds fed with emulsified diets. However, compensation effect to recover the energy value to control level was not found. Significant reduction (P<0.05) in liver fat, abdominal fat and digesta fat was observed in birds which consumed emulsified grower diets. However, no significant difference between synthetic emulsifier and natural biosurfactant was observed.